Controversy over the Law of Scolding the Dead; Thematic Study of Hadith - Wiwik Halwiyah (Taqriri: Journal of Al-Hadith Science Studies, 2026)
Respecting others is a behavioral pattern established in Islamic law to uphold human dignity. The antonym of this act is cursing, which is clearly prohibited in Surah al-Hujurāt: 11. The prohibition against cursing others is not only directed at living people but also at the deceased, as stated in the hadith. However, the author also found hadith indicating the permissibility of cursing the deceased, making the two aspects and their overt intent contradictory. The author used a qualitative method with a descriptive-analytical approach and content analysis. This research aimed to answer the following research questions: How is the wording of hadiths on cursing the deceased interpreted? And how is the interpretation of these hadiths analyzed? The aim was to identify and analyze these hadiths to extract their essence and implied meaning. This research provides an understanding that the hadiths on this topic are not contradictory, but rather point to the specificity within the generality. Furthermore, the law prohibits cursing the deceased, except in certain aspects that trigger public interest, such as testimony.